Improving Bank Transparency in Assessing Financial Stability of Ukraine’s Banking System - Ptashchenko, Liana; Volkova, Nelia; Volkova, Valeriia (International Journal of Engineering and Technology, 2018)
The paper focuses on solving the problem of banks transparency in assessing financial stability of Ukraine’s banking system under economic instability. The financial crisis in the country calls for developing a methodology supply for assessing financial stability of both individual banks and the banking system as a whole. We believe that the methodical tool for studying the financial activity of a banking institution should provide a bank with the opportunity for a long-term development rather than for the coming years. This is a priority task of a bank because under unstable economic development the reliability of a bank decreases as well as its competitiveness and adaptability to the internal and external destabilizing factors. The topicality of the issue is determined by the fact that increasing financial sustainability is one of the important measures, the quality of which predetermines banks’ financial results. Presented are results of the statistics study which characterize the development of the modern banking system. It is ascertained that within asymmetry of information the transparency level is critical in assessing financial stability of banks which is still given poor consideration in our country. The authors believe that the use of the suggested tool for determining banks’ transparency level in bank’s operation will help impartially assess its transparency level, will promote the development of channels of information disclosure to external users. It is rationalized that effective banking activity in Ukraine can ensure the recovery of the financial sector and restore the growth rates of the real sector of the country’s economy. The authors’ concept of increasing banks’ transparency in assessing financial stability of the Ukrainian banking system proves that it is the basic condition for maintaining bank’s favorable potential and effective performance. For the first time systematized are the characteristic features of transparency when analysing the transparency of the banking system as a whole. Distinguished is the expediency of using a certain set of tools and information disclosure channels in implementing the mechanism of transparency at different levels of the banking system. A conclusion is made that it is necessary to increase the transparency of banks in assessing the financial stability of the banking system of Ukraine, namely: ensuring information transparency of the bank will help to increase the confidence of market participants and provide an opportunity for the bank to expand its resource base, increase income and profits.
Keywords: asymmetry of information; financial stability; potential; profitability; transparency; risk; strategic vector